Impact of a Digital Repository on Producing e-Courses for Mathematics Teachers - Alibraheim, Essa A.; Hassan, Hassan F.; Soliman, Mohamed W. (International Journal of Learning, Teaching and Educational Research, 2022)
In light of the rapid and increasing spread of technology in all aspects of life, developing the skills for producing e-courses for teachers has become an important need. This empirical research aims at designing a digital repository based on interactive learning objects and measuring its impact on developing the skills necessary for producing e-courses based on Quality Matters (QM) standards for middle school mathematics teachers. We apply both a descriptive analytical approach and an experimental approach to achieve this objective. This empirical research was conducted on a random sample of 60 schoolteachers, who were randomly divided into two groups: an experimental one, consisting of 30 schoolteachers who were trained using the digital repository based on interactive learning objects; and the control, consisting of 30 schoolteachers who were trained using the traditional training method. The research tools consisted of an achievement test and a quality assessment card for e-courses based on QM standards. To analyse the data, an independent sample t-test was used. The results revealed that, in contrast with the control group, the experimental group acquired superior skills in designing and producing e-courses, as well as in the quality of e-courses. These results confirm the importance of using digital repositories based on interactive learning objects as one of the modern directions for future development in the production of e-courses based on QM standards for middle school teachers. https://doi.org/10.26803/ijlter.21.9.10